INFORMATION MANAGEMENT WEB PROCESS WEDDING BUILDING RENTAL - Dwi Sukma Donoriyanto; Rus Indiyanto; Rana Atikah Ardlianti; Siswanto Moenandar; Naniek Ratni Juliardi A.R; Yuliatin Ali Syamsiah (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2023)
In this modern era, convenience is what makes competition in the building rental business increase. Therefore, every business actor is required to have a good management information system. One way to make a good system is to implement it in web form. Yutanila Wedding is a wedding hall rental service. This study aims to create a web-based building rental management information system. The research was conducted from designing databases to web hosting processes using Power Designer, Xamp, and Dreamweaver software. From the research results, we get a website for renting wedding halls that is used for the building rental process. The web contains how the login process, data input, and output data are generated. Thus, the web can be used by the public with the available web links